Analisis Pengaruh Input Nilai Kalor Batubara Terhadap Kinerja Boiler Tipe CFB Pada PLTU PT. Antam Tbk - Jumadi Tangko; Yiyin Klistafani; Esra Marten (Politeknik Negeri Ujung Pandang, 2022)
boiler is a closed vessel where the heat of combustion is transferred to the water until it forms hot steam or steam. The boiler used in the PT ANTAM PLTU is a CFB type, where the operator at the PLTU ANTAM Tbk performs heating value input to determine the amount of coal and combustion air used. The analysis of the effect of the input heating value is expected to be taken into consideration in knowing the effect of the heating value input which is different from the heating value of coal supplied to the furnace, which is viewed from the side of pressure and temperature, which affects the physical boiler, boiler work efficiency, heat losses in the boiler. and also boiler life time. From the results of research and analysis of efficiency calculations where there is the largest difference in the value of efficiency directly at 1.161935% at the start of operation and 1.20276% in March 2020 between calculations with GCV of coal and input of heating value. Meanwhile, the largest difference in efficiency was indirectly 0.085689% at the start of operation and 0.09224% in March 2020. Meanwhile, the largest difference in total heat losses at the beginning of operation was 0.09245% and in March 2020 was 0.69317%.Â